Праздник своими руками. От совета до сценария: изд. для досуга / Е. А. Воронова - Воронова Елена Александровна (Зажигаем, 2006)
На обл. авт. не указан Экземпляры: аб. ДБ (20181213) / Инвентарный номер: 5935 / Цена: / Сис.шифр: 74 / Авт.знак: В 75 / ГРНТИ: 14.25.19 / ББК: 74.200.551 я92